Women and Development Unit - Singh Santiago (Al-Qanṭara, 2022)
By emphasizing the role of the Enlightenment in the origins of feminism, I intend to make a distinction between political feminist literature, on the one hand, and another train of thought, also polemic, that has cropped up recurrently in European history since the thirteenth century. At the dawn of the early Middle Ages, at the time of the birth and spread of Gothic city life and early medieval forms of civilization, an entirely new set of ways and ideas was born which may be summed up by the term gallantry. In that context a particular form of literature emerged – I will refer to it as “discourse on the excellence of noble women” – which was cultivated by both men and women and unquestionably had its social uses. It served to provide models of female conduct and reinforce the self- esteem of women in the noble castes. By referring to queens, heroines, female saints, and other great women of the past, it offered models of femininity that contributed to the creation of gallantry among the group in power. However, this discourse on the excellence of women did not go unchallenged: it was paralleled by a misogynous literature of remote origins, usually promoted by the clergy but sometimes also by lay authors. The discourse on the excellence of women and the misogynous discourse competed with one another in an almost ritualised performance up until the Baroque period. The one exalted the feminine virtues and qualities and cited women as examples, while the other, with origins that went back to the Fathers of the Church and even to Aristotle, harped relentlessly on the supposed shortcomings and inherent stupidity of the female sex. Philogynists and misogynists kept repeating the same examples and arguments without ever coming to agreement, or perhaps never intending to, in an endless debate. However, they both shared, and neither of them ever challenged, the premise that women had to be under the authority of men; they differed only on the respect that should be accorded to them.